The effect of packaging materials on physicochemical, microbiological, and sensorial properties of Turkish whey (Lor) cheese with some plants. Issue 11 (6th September 2022) - Akpinar, Asli; Yerlikaya, Oktay; Akan, Ecem; Karagozlu, Cem; Kinik, Ozer; Uysal, Harun Rasit
Abstract: In this study, 2% black cumin, 1% black cumin ( Nigella damascena L–Damascus black cumin), 1% rosemary ( Rosemarinus officinalis ), and 1% black cumin and 1% thyme ( Origanum onites L.–Izmir thyme) were added to whey cheese with a short shelf life and cheese samples stored in different packaging materials (goat‐skin bags and artificial casing). pH levels and titratable acidity, degree of proteolysis, microbiological, and sensory attributes of the samples were examined. In 20 days of storage, the pH values of whey cheese with black cumin stored in goat‐skin bags were statistically higher (ranged 6.34–5.30) than other samples (ranged 6.32–4.10). Proteolytic activity values were higher (0.34–0.58 mg/ml serine) in cheese samples containing black cumin and thyme in both packaging materials ( p  < .05). After 30 days of storage, black cumin and thyme‐added cheese packaged in goat‐skin bags have the highest Lactobacillus spp. count (8.64 log CFU/g), while cheese containing black cumin and thyme (6.32 log CFU/g) filled into an artificial casing has the least. Based on the results of sensory analysis, the samples containing black cumin were generally more preferred while cheese with rosemary had the lowest sensory scores. In conclusion, the difference in packaging materials has a significant effect on the physicochemical and microbiology properties and proteolytic activity of whey cheese produced by adding different plants. However, the sensory properties of whey cheese are influenced by the plants used rather than the differences in packaging materials. Novelty impact statement: Turkish whey (Lor) cheese is food with limited storage time and rapid microbial spoilage. Black cumin, rosemary, and thyme were added to whey cheese. Black cumin, rosemary, and thyme have been added to whey cheese and this limited storage period has been tried to be extended. In addition, the effects of goat‐skin and artificial casing packages on physicochemical and sensory properties were investigated.